Does Concern Motivate Behavior Change?: Exploring the Relationship Between Physical Activity and Body Mass Index Among Low-Income Housing Residents. (December 2014) - Tamers, Sara L.; Allen, Jennifer; Yang, May; Stoddard, Anne; Harley, Amy; Sorensen, Glorian
Objective . To explore relationships between concerns and physical activity and body mass index (BMI) among a racially/ethnically diverse low-income population. Method . A cross-sectional survey documented behavioral risks among racially/ethnically diverse low-income residents in the Boston area (2005-2009). Multivariable logistic regressions were conducted in 2012 for each concern, using SAS version 9.2. Results . Those very/moderately concerned about weight were more likely to have higher BMIs, be in the preparation/action stage, received behavioral counseling, participated in a weight management program, and be interested in participating in one in the future. Those very/moderately concerned about physical activity were more likely to have higher BMIs, received behavioral counseling, and participated in a physical activity program. Conclusion . Individuals with elevated BMIs or low levels of physical activity are concerned. While level of concern is important, these findings suggest that it is not likely to be a sufficient catalyst to behavior change.